TRADITIONAL CHINESE MEDICINE COMBINED WITH HORMONE THERAPY TO TREAT PREMATURE OVARIAN FAILURE: A META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS - Kou, Mei-Jing; Ding, Xiufang; Chen, Jia-Xu; Liu, Yan; Liu, Yue-Yun (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: This meta-analysis aimed to provide critically estimated evidence for the advantages and disadvantages of Chinese herbal medicines used for premature ovarian failure (POF), which could provide suggestions for rational treatments. Materials and Methods: The databases searched included MEDLINE, EMBASE, CNKI, VIP, China Dissertation Database, China Important Conference Papers Database, and online clinical trial registry websites. Published and unpublished randomized controlled trials of traditional Chinese medicine (TCM) combined with hormone therapy (HT) and HT alone for POF were assessed up to December 30, 2015. Two authors extracted data and assessed trial quality independently using Cochrane systematic review methods. Meta-analysis was used to quantitatively describe serum hormone levels and Kupperman scores associated with perimenopause symptoms. Results: Seventeen randomized controlled trials involving 1352 participants were selected. Compared with HT alone, although no significant effects were observed in the levels of luteinizing hormone, therapy with TCM combined with HT compared to HT alone effectively altered serum hormone levels of follicle stimulating hormone (P<0.01) and estradiol (P < 0.01), and improved Kupperman index scores (P< 0.01). Conclusions: The reported favorable effects of TCM combined with HT for treating POF patients are better than HT alone.However,the beneficial effects derived from this combination therapy cannot be viewed conclusive.In order to better support the clinical use, more rigorously designed trials are required to provide